BK 306: A two-row barley (Hordeum vulgare L) as potential source of higher diastatic power and FAN content for malt barley improvement - Kumar, Dinesh; Verma, Ramesh Pal Singh; Khippal, Anil Kumar; Kharub, Ajit Singh; Singh, Charan; Singh, Gyanendra Pratap (Journal of Cereal Research, 2022)
The Indian malt industry has updated the specifications in past few years with respect to the diastatic power of the malt and free amino nitrogen content in the wort. The demand is now for higher values of malt diastatic power for better degradation of starch during the malting and brewing processes. Similarly, higher values of free amino nitrogen (FAN) content are preferred for better yeast growth during the brewing operations. We hereby report a genotype BK 306, which posses’ higher diastatic power (average of 107°L) and FAN content (average of 216 ppm) as compared to the prevalent two row malt barley varieties. The genotype can be a potential source for these two traits for malt barley improvement programme of the country.